PENGARUH KEMUDAHAN PENGGUNAAN M-BANKING DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF GENERASI Z - Maharani Safira; Rio Maryono; Desi Edliawati; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
Consumptive behavior can arise inseparable from conditions of technological development which provide significant changes to human life. One of them is the ease of accessing everything. This research aims to determine and analyze the influence of User Ease and Lifestyle variables on Consumptive Behavior in Generation Z in Kab. Bekasi. To determine the sample in this study, Purposive Sampling Technique was used with the criteria for a population size using the moe formula of 100 respondents. The results of this research show that there is a fairly strong correlation between ease of use and lifestyle. This indicates that the ease of use of BCA mobile is closely related to the lifestyle of generation Z who is digitally connected and has a preference for comfort and flexibility. The ease of use of BCA mobile provides a practical and efficient solution in managing daily finances.